Spór między saintsimonistami a furierystami o własność ziemi w kolonialnej Algierii w XIX wieku - Popowicz, Kamil (Civitas. Studia z filozofii polityki, 2019)
In the nineteenth century, the French utopian socialists, Saint-Simonians and Fourierists, developed different concepts of the colonisation of Africa. These concepts collided in Algeria. The Saint-Simonians were impressed by the Arab system of the tribal ownership of land. They wanted to preserve it and ultimately bring the two peoples, the Arabs and the French, together in the spirit of a commune. On the other hand, the Fourierists wanted to expropriate Arabs from their land and hand it over to the French colonists so that they could build new economic communities of a phalanstery type. This article presents the theoretical disputes between the two schools and also describes the actual practical consequences of these disputes for the French colonial politics.